2022
DOI: 10.1088/2752-5724/ac8a63
|View full text |Cite
|
Sign up to set email alerts
|

Scanning probe microscopy in probing low-dimensional carbon-based nanostructures and nanomaterials

Abstract: Carbon, as an indispensable chemical element on Earth, has diverse covalent bonding ability, which enables construction of extensive pivotal carbon-based structures in multiple scientific fields. The extraordinary physicochemical properties presented by pioneering synthetic carbon allotropes, typically including fullerenes, carbon nanotubes, and graphene, have stimulated broad interest in fabrication of carbon-based nanostructures and nanomaterials. Accurate regulation of topology, size, and shape, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 196 publications
0
11
0
Order By: Relevance
“…[ 4–8 ] They have manifested a series of advantages including naturally‐passivated surface, thickness/strain/torsion‐regulated bandgap, excellent in‐plane carrier mobility, Si‐complementary metal‐oxide–semiconductor processing compatibility, outstanding flexibility, etc. Thus far, hundreds of 2DLMs have been explored including elemental semiconductors and their derivatives, [ 9–13 ] nitrides, [ 14 ] phosphides, [ 15,16 ] transition metal dichalcogenides, [ 17–28 ] post transition metal chalcogenides, [ 29–35 ] transition metal halides, [ 36–38 ] solid solutions, [ 39 ] multi‐element compounds, [ 40–56 ] topological insulators, [ 57,58 ] alloys, [ 59 ] etc. Their bandgap values range from 0 up to 6 eV, theoretically enabling them to meet the diverse practical applications in various wavebands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4–8 ] They have manifested a series of advantages including naturally‐passivated surface, thickness/strain/torsion‐regulated bandgap, excellent in‐plane carrier mobility, Si‐complementary metal‐oxide–semiconductor processing compatibility, outstanding flexibility, etc. Thus far, hundreds of 2DLMs have been explored including elemental semiconductors and their derivatives, [ 9–13 ] nitrides, [ 14 ] phosphides, [ 15,16 ] transition metal dichalcogenides, [ 17–28 ] post transition metal chalcogenides, [ 29–35 ] transition metal halides, [ 36–38 ] solid solutions, [ 39 ] multi‐element compounds, [ 40–56 ] topological insulators, [ 57,58 ] alloys, [ 59 ] etc. Their bandgap values range from 0 up to 6 eV, theoretically enabling them to meet the diverse practical applications in various wavebands.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] They have manifested a series of advantages including naturally-passivated surface, thickness/strain/torsion-regulated bandgap, excellent in-plane carrier mobility, Si-complementary metal-oxidesemiconductor processing compatibility, outstanding flexibility, etc. Thus far, hundreds of 2DLMs have been explored including elemental semiconductors and their derivatives, [9][10][11][12][13] nitrides, [14] phosphides, [15,16] transition metal dichalcogenides, [17][18][19][20][21][22][23][24][25][26][27][28] post transition metal chalcogenides, [29][30][31][32][33][34][35] transition metal halides, [36][37][38] solid solutions, [39] multi-element compounds, [40][41][42][43][44][45][46][47][48][49][50]…”
Section: Introductionmentioning
confidence: 99%
“…1 It has also attracted great attention from the surface science community as a versatile strategy to construct C-C bonds and corresponding carbon-based nanoarchitectures via on-surface synthesis. 2 Moreover, by means of in situ characterization techniques, such as scanning tunneling microscopy (STM) and atomic force microscopy (AFM), 3 sets of intermediates, generally classified into surface-stabilized radicals and organometallic intermediates, have been successfully captured on surfaces and visualized in real space, [4][5][6] which is usually a great challenge in traditional organic synthetic chemistry. As early as 2000, Hla et al reported deiodination and sequential coupling processes (i.e., Ullmann reaction) on surface with all elementary steps controllably triggered by STM tip manipulations and intermediates captured.…”
mentioning
confidence: 99%
“…In the pioneering work of the OSS field, Grill et al first achieved on-surface Ullmann homocoupling in 2007 and demonstrated that on-surface covalent architectures are artificially programmed into one-dimensional nanowires or two-dimensional networks by changing the position of the reactive groups in the precursors and controlling the reaction hierarchy by varying the type of reactive groups . Subsequently, a variety of OSS methods have been developed to generate predictable covalent structures, whether via thermal activation on catalytic metal surfaces or other types of activation on nonmetal surfaces. ,, These methods have enabled the production of one- and two-dimensional large carbon nanosystems with atomic precision that are inaccessible in solution due to their poor solubility.…”
mentioning
confidence: 99%